Pattern Recognition by CD6: A Scavenger-Like Lymphocyte Receptor - Sarukhan, Adelaida; Martinez-Florensa, Mario; Escoda-Ferran, Cristina; Carrasco, Esther; Carreras, Esther; Lozano, Francisco (Current Drug Targets, 2016)
CD6, one of the first antigens to be identified on T cells, is a membrane glycoprotein that physically associates with the antigen receptor complex. Because of this, its main function seems to involve the modulation of TCR-mediated signaling pathways. However, growing evidence indicates that this ancient and conserved scavenger-like receptor may also play a role as pattern recognition receptor (PRR), similar to other members of the scavenger receptor cysteine rich superfamily (SRCR-SF). Here, we discuss the functional interactions of CD6 with microbe- and damage-associated signals and the potential use of soluble forms of CD6 in the therapeutic treatment of bacterial infections, in particular multi-drug resistant bacterial strains. Importantly, microbe recognition by CD6 may also have functional consequences on T cell activation and differentiation, which remain to be explored.
Keywords: Bacteria